Chronic venous disease patients show increased IRS-4 expression in the great saphenous vein wall. Issue 9 (September 2021) - Ortega, Miguel A; Fraile-Martínez, Oscar; García-Montero, Cielo; Ruiz-Grande, Fernando; Barrena, Silve; Montoya, Hector; Pekarek, Leonel; Zoullas, Sofia; Alvarez-Mon, Miguel A; Sainz, Felipe; Asúnsolo, Angel; Acero, Julio; et al.
Objectives: Chronic venous disease (CVeD) is a multifactorial and debilitating condition that has a high prevalence in Western countries and an important associated socioeconomic burden. Varicose veins (VVs) are the most common manifestations of CVeD. Pathologically, many morphological and functional changes have been described in VVs, which most notably affect venous wall integrity. Previous studies have found several molecular alterations that negatively affect normal cell signaling pathways. Insulin receptor substrate (IRS)-4 is a central adaptor protein that is closely related to insulin/insulin-like growth factor-1 signaling upstream, phosphatidylinositol 3-kinase/Akt or mitogen-activated protein kinases downstream, and other proteins. These molecular pathways have been implicated in CVeD pathogenesis. Thus, the aim of our study was to identify the role of IRS-4 in VV tissue. Methods: We conducted a histopathological study to analyze IRS-4 protein expression in CVeD patients compared with healthy controls. Results: Our results demonstrate a significant increase in IRS-4 expression in VV tissue. Conclusions: IRS-4 may be implicated in CVeD development and progression. Therefore, IRS-4 could be a potential diagnostic or therapeutic target for patients with this condition.